Effect of fiber orientation and ply stacking sequence on buckling behaviour of basalt-carbon hybrid composite laminates - Dhuban, S.B. (National Institute of Science Communication and Information Resources (NISCAIR), 2017)
The aim of this study is to investigate the effect of fiber orientation and ply stacking sequence of basalt-carbon hybrid composite laminates on the critical buckling strength, experimentally and by using nonlinear finite element analysis. The composite laminated plates are simply supported and subjected to axial compression load. Nonlinear FEA results using ANSYS have good agreement with the experimental results. FEA results showed that the outer layers have the most significant influence on the buckling strength of the composite laminated material. Furthermore, placing carbon fiber reinforced layers in the outer surface of the basalt-carbon/epoxy hybrid laminates results in significant increase in the critical buckling load compared to placing basalt fiber reinforced layers in the outer surface. It is also concluded that 0 2 C/0B/+45B S laminate is the best combination of the hybrid stacking sequences as far as buckling strength is concerned. © 2017, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.